CBCT INVESTIGATION OF THE INTRABONY CANAL COMMUNICATIONS BETWEEN THE VESTIBULAR AND LINGUAL PLATES IN THE ANTERIOR MANDIBLE - Dimitar Yovchev; Hristina Mihaylova; Elitsa Deliverska; Nadezhda Miteva - Yovcheva (Peytchinski Publishing, 2020)
Purpose: To assess the presence of the vestibulo - lingual intrabony canal communications (VLC) in the anterior mandible using cone beam computed tomography (CBCT). Materials and methods: Study material included 200 CBCT scans taken for preoperative planning of implant placement. The images were examined carefully by three observers concerning the presence of VLC. Interobserver agreement in identification of the canal communications was excellent (mean kappa value - 0.82). Results: Vestibulo - lingual communications were found in 27 % of cases. The communications appeared as a crossing of the lateral lingual canal with the mandibular incisive canal (type 1), as a connection between midline lingual canal (or canals) and a vestibular nutrient canal (type 2) or as a lateral lingual canal connected with the anterior loop of the mandibular canal (type 3). The main type of VLC is those between a lateral lingual canal and mandibular incisive canal - 85.2% from all of the VLCs. Conclusions: A considerable part (27%) of Bulgarian citizens has vestibulo - lingual communications in the anterior mandible. The type 1 communication prevails, and it is more frequently located on the right side. The knowledge about vestibulo - lingual communications could contribute a better understanding of bone tumor invasion but further studies are necessary.